Syngas Characteristics from UCG Gasification Process with Lignite and Subbituminous Coal Types - Sarmidi; Muhammad Yerizam; Aida Syarif (International Journal of Research in Vocational Studies (IJRVOCAS), 2021)
Underground Coal Gasification (UCG) is the process of converting the materials used to make synthetic gas in a feasible and economically attractive manner as a method for harnessing energy from underground coal sources. Coal gasification will produce a gas producer in the form of synthetic gas (syngas) with the main components consisting of carbon monoxide (CO), hydrogen (H2), carbon dioxide (CO2) and nitrogen (N2) and low pollutants. The highest temperature produced with MT 47 lignite coal using an oxygen velocity of 5 liters/minute was 2400 C at the 35th minute, while the lowest temperature was 950 C at the 95th minute. For Subbituminous AL 51 coal using an oxygen velocity of 5 liters/minute, the highest temperature is 3540 C at 75 minutes, while the lowest temperature is 1060 C at 130 minutes. At an oxygen velocity of 5 liters/minute the flash point / burn test is on the MT 47 lignite coal type in the 10th minute and at a temperature of 1700 C. Meanwhile, the AL 51 subbituminous coal type is in the 30th minute and at a temperature of 3130 C. Based on the discussion and analysis of data from the gasification test of lignite and subbituminous coal with variations in oxygen velocity of 5 liters/minute, the results obtained are that lignite coal burns faster (burn test) in the 10th minute at a temperature of 1700 C, in the subbituminous type it has higher temperature 3130 C and longer burn test at 30 minutes.